A study of wave reflection based on the maximum wave momentum flux approach. Issue 1 (2nd January 2018) - Buccino, M.; D'Anna, M.; Calabrese, Mario
ABSTRACT: Based on the maximum wave momentum flux approach (MFA) originally proposed by Hughes, simple predictive equations for the reflection coefficient of sloping coastal structures have been developed. The design tools permit either estimating the "bulk" reflection coefficient or reconstructing the entire reflected wave spectrum. A comparison with nearly 1, 600 results of physical model studies carried out in different laboratories around the world indicated the new method to be rather effective, especially in the case of permeable structures.